P–094 Kidney function impairment in primary infertile men. (6th August 2021) - Fallara, G; Boeri, L; Candela, L; Pozzi, E; Belladelli, F; Capogrosso, P; Cazzaniga, W; Ventimiglia, E; Schifano, N; Costa, A; Cignoli, D; Cornelius, J; et al.
Abstract: Study question: We investigated the prevalence of kidney function impairment in a homogeneous cohort of white-European primary infertile men. Summary answer: Mild kidney function impairment characteristics were found in 9% of asymptomatic and unaware patients presenting for primary infertility investigation. What is known already: Infertile men have shown a worse overall health status compared to the fertile counterpart. We investigated the prevalence of kidney function impairment in a homogeneous cohort of white-European primary infertile men. Study design, size, duration: In this corss-sectional study, complete clinical and laboratories data from a cohort of 557 consecutive men aged >18 years, presenting for primary infertility investigation were analyzed. Participants/materials, setting, methods: Comorbidities (as scored with the Charlson Comorbidity Index (CCI)) were collected in each patient. Primary outcome was the presence of functional impairment of the kidney (defined as an estimated glomerular filtration rates <90 ml/min/1.73m², according to the Kidney Outcomes Quality Initiative). The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) function was used for eGFR calculation. Logistic regression analyses tested the association between kidney function impairment and clinical and semen features. Main results and the role of chance: Of 557, 51 (9.3%) patients depicted at least a mild loss of kidney function (eGFR<90 ml/min /1.73m²). Median [interquartile (IQR)] age was 38 (35–42) years for normal kidney function group vs. 41 (36–46.5) years for those with impaired renal function (p < 0.001). Those with impaired renal function had also a higher BMI [26.1 (24.4–27.8) vs. 24.9 (23.2–26.8); p = 0.002] and higher numbers of comorbidities [CCI≥ 1 in 11 (21.5%) vs. 40 (7.9%) patients (p < 0.001)]. Of note, they had more frequently history of hypertension [10 (19.6%) vs. 31 (6.1%), p = 0.001]. Groups did not differ in terms of hormonal and semen features. At logistic regression analysis, older age and CCI≥1 were associated with a higher risk of impaired eGFR (OR 1.06; 95%CI 1.01–1.11; p = 0.016 and OR 2.41; 95%CI 1.06–5.15; p = 0.028, respectively)(table). No association was found between sperm parameters and eGFR impairment (all p > 0.05), after accounting for age, CCI, BMI, FSH, testicular volume, and varicocele. Limitations, reasons for caution: Mild kidney function impairment characteristics were found in 9% of asymptomatic and unaware patients presenting for primary infertility investigation. Age and the rate of comorbidities are associated with reduced eGFR. Wider implications of the findings: This novel finding confirms growing data on a significant association of male infertility with a poorer overall male health status. Trial registration number: Not applicable